As dinâmicas corporais na docência com bebês - Silva, Isabel Rodrigues da (2018)
The present research, at Masters level, aimed to analyze the composition of body dynamics in teaching with babies. The specific objectives that were delimited from the cited subject are: Understanding the corporal demands and dynamic’s specificities during educating actions, as well as to analyze how the teacher’s dynamics and corporal demands are defined by the babies’ physical needs and; gather elements to understand how the emotional-body-care contributes to the teacher’s activity. In order to achieve the spoken objectives, an ethnographic field research was carried out on a group composed by 12 children and two teachers from an public early childhood education institution, which is located in the municipality of São José. Data were generated through observation, written records, audiovisual and photographic recordings, during a four month period, two up to three times a week during the afternoon, and based on authors such as: Cohn (2005), Corsaro (2011), Geertz (1989), Graue e Walsh (2003), Lopes (2004). Bardin’s (2011) and Vala’s (1999) Content Analysis Technique was used for data organization which resulted in four analysis categories: 1) The teacher’s body when attending to singularities in a collective context; 2) The teacher's body that calms and embraces; 3) The teacher's body as a possibility of relationship and; 4) Unhurried relationships versus intense body movement and influence of materials. The theoretical framework used to guide the data analysis was based on studies in the field of Child Anthropology, Childhood Sociology and Childhood Pedagogy. A dialogue with the recent scientific productions on the subject was used for the analyzes, as well as studies from Buss-Simão (2012, 2016), Duarte (2011), Giddens (2005), Foucault (2004, 2010), Le Breton (2006, 2009), Norbert Elias (2011), Sabbag (2017), Schmitt (2008, 2014), Tardif (2001), Tardif e Lessard (2013), Tardos (1992), Teixeira (2007), Tristão (2004), Vigarello (2003) e Wallon (1971, 1975). The analyzes have revealed that the dynamics and body demands for teaching infants are influenced by the infants’ body demands. While responding and embracing the infants’ demands, teachers reveal an intense physical availability that, through relationship, constitutes the babies socially and culturally. The analyzes also showed that the attendance to singularities, which are constant when teaching infants, occupy a great part of the educator’s time, remarked by its intense corporal relations, these encounters are, in turn, intermittent, whereas other babies also seek this relationship. Data also revealed that, in order to meet the babies’ demands, while involved in a temporality imposed by both babies and the institution, which often hasten assisting the infants’ singularities, Educators use intense body movement in order to speed up the assistance, at the same time as they seek to respect the babies’ body and time. Resulting from the agility needed, teachers often do not pay attention to their own body while performing movements, revealing an oversight related to their own physique, which, by the end, generates a physical exhaustion, a body fatigue. The data also reveals that weariness and fatigue, caused by teacher’s self body carelessness, intensifies through the use of inappropriate materials.